2007
DOI: 10.1007/s00436-007-0522-y
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on synanthropic flies (e.g. Musca, Sarcophaga, Calliphora, Fannia, Lucilia, Stomoxys) as vectors of pathogenic microorganisms

Abstract: In the present study, different fly species were associated with foodborne and other pathogens. Wild synanthropic flies belonging to 12 species of 12 genera were caught for the isolation and identification of microorganisms, which might have been possibly transmitted by these flies. Trapping of flies was done at different domestic animal related places (dog pound, poultry house, cattle barn, horse stable, pigpen). All 56 individual flies were shown to be carriers of multiple species of microorganisms. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(100 citation statements)
references
References 14 publications
3
88
1
8
Order By: Relevance
“…Multiple species of bacteria were isolated from a majority of the flies (98.64%) of the flies collected in the study indicating that this fly species is a potential mechanical vector of multiple pathogens. This has been previously suggested in reports by Greenberg [7] and Förster et al [20]. Most of the bacteria recovered from this fly species are important human pathogens, known to produce diseases such as food poisoning, diarrhea and skin infection in humans and animals.…”
Section: Discussionsupporting
confidence: 61%
“…Multiple species of bacteria were isolated from a majority of the flies (98.64%) of the flies collected in the study indicating that this fly species is a potential mechanical vector of multiple pathogens. This has been previously suggested in reports by Greenberg [7] and Förster et al [20]. Most of the bacteria recovered from this fly species are important human pathogens, known to produce diseases such as food poisoning, diarrhea and skin infection in humans and animals.…”
Section: Discussionsupporting
confidence: 61%
“…They move between feces and carcasses and food meant for human consumption. Bacteria acquired from filth can be transmitted to food, either via the fly exterior, e.g., body surface and mouth parts, or with feces and vomit that is produced during feeding (18)(19)(20)(21)(22)(23). In an experimental setting, flies were shown to transmit Campylobacter between chickens (24), and several studies have demonstrated similar pathogenic E. coli and Klebsiella strains on flies and in humans in hospital settings, as well as in small rural communities, suggesting their potential as transmission vehicles (25)(26)(27).…”
mentioning
confidence: 99%
“…Most species of Calliphora are well known because of their medical and forensic importance (James 1947;Nuorteva 1963;Zumpt 1965;Greenberg 1971;Smith 1986;Greenberg & Kunich 2002;Graczyk et al 2005;Sawabe et al 2006;Förster et al 2007;Byrd & Castner 2010;Salvetti et al 2012).…”
Section: Introductionmentioning
confidence: 99%